1983
DOI: 10.1071/bi9830351
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicles of New-born Merino Lambs from Genetic Lines which Differ in Fecundity

Abstract: Ovaries were obtained from 78 new-born lambs (12 singletons, 25 twins, 28 triplets, 10 quadruplets and 3 quintuplets) from flocks selected for (T902, T903 and Booroola) or against (0) multiple births. Sections of the ovaries were examined with a projection microscope and the numbers of all types of follicles were estimated. There were no differences between genetic lines in the number of primordial follicles, after adjustment for litter size and sire; however, there were significantly more of these follicles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
1
9
1
Order By: Relevance
“…However, responses to shortterm lupin supplementation are variable and largely dependent on the ovarian population of antral follicles (Gherardi & Lindsay 1982, Leury et al 1990, Nottle et al 1997, Viñ oles et al 2010b. In ewes, the population of antral follicles is affected by several factors, including genotype and body condition (Tassell et al 1983, Viñ oles et al 1999, and perhaps the perinatal nutritional history of their mother.…”
Section: Introductionmentioning
confidence: 99%
“…However, responses to shortterm lupin supplementation are variable and largely dependent on the ovarian population of antral follicles (Gherardi & Lindsay 1982, Leury et al 1990, Nottle et al 1997, Viñ oles et al 2010b. In ewes, the population of antral follicles is affected by several factors, including genotype and body condition (Tassell et al 1983, Viñ oles et al 1999, and perhaps the perinatal nutritional history of their mother.…”
Section: Introductionmentioning
confidence: 99%
“…3 (1978) reported that 4-week-old Merino lambs contained antral follicles > 1 mm in diameter. On the other hand, newborn Booroola-Merino lambs had fewer antral follicles than did control Merino lambs (Tassell et al, 1983) and 1-month-old Booroola-Assaf ewe lambs had smaller ovaries and fewer antral follicles than did Assaf lambs (Braw-Tal et al, 1988). Our results suggest that the structure of the ovary of the lamb might be influenced by the F gene, although the possibility that other components of the Booroola genotype may be also responsible cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive physiology of Booroola-Merino and Booroola-Romney ewes has been exten¬ sively studied during recent years (Bindon et al, 1985a; McNatty . It has been shown that Booroola ewe lambs are characterized by elevated basal plasma FSH concentration between 3 and 6 weeks of age (Findlay & Bindon, 1976;Bindon et al, 1985b) and it has been suggested that differences in ovarian feed-back regulation of FSH, which is known to be operative by this age, is responsible for this phenomenon (Tassell et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Interested readers are referred to reports by Bindon (1975Bindon ( , 1984, Piper (1976b, 1977), Piper et al (1976), Piper and Bindon (1983), Tassell et al (1983), Owens et al (1984), Owens et al (1985b), Robertson et al (1984), Bindon et al (1986), Fry et al (1987), Kind et al (1988) and Driancourt et al (1990).…”
Section: Booroola Merino Researchmentioning
confidence: 99%